PARTISIPASI MASYARAKAT DALAM PENGELOLAAN PARIWISATA COBAN TALUN DI DESA TULUNGREJO KOTA BATU - Ambung, Sarida; Kurniawati, Dwi; Sakdiyah, Siti Halimatus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine community participation in the management of Coban Talun tourism and the form of tourism management in Tulungrejo Village, Batu City. The method used is descriptive qualitative through observation, interviews, and documentation. The results of the study indicate that community participation is active, comprehensive, and sustainable, with involvement in the form of ideas, energy, expertise, and material and financial support at all stages of management, namely planning, implementation, utilization, and evaluation. The community plays a key role in the development of locally-based tourism. In addition, tourism management is carried out collaboratively based on local wisdom through cooperation between the community, village government, and BUMDes in infrastructure development, environmental and cultural preservation, attraction development, and inclusive tourism services. This creates sustainable management, improves community welfare, and preserves the local nature and culture.